2015
DOI: 10.3389/fnhum.2015.00344
|View full text |Cite
|
Sign up to set email alerts
|

The Neurobiology and Psychology of Pedophilia: Recent Advances and Challenges

Abstract: A pedophilic disorder is recognized for its impairment to the individual and for the harm it may cause to others. Pedophilia is often considered a side issue and research into the nature of pedophilia is delayed in comparison to research into other psychiatric disorders. However, with the increasing use of neuroimaging techniques, such as functional and structural magnetic resonance imaging (sMRI, fMRI), together with neuropsychological studies, we are increasing our knowledge of predisposing and accompanying … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
86
1
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 112 publications
(102 citation statements)
references
References 167 publications
(256 reference statements)
1
86
1
3
Order By: Relevance
“…However, these earlier studies did not distinguish between pedophilia and child sexual abuse. Recent reviews and meta-analyses investigating differences between individuals sexually oriented toward children and individuals sexually oriented toward adults revealed that their brain structures are very similar in nature (17,62,63). As indicated by two recent studies, aberrant neuroanatomy might rather be associated with child sexual abuse than with pedophilia (64,65).…”
Section: Structural Imagingmentioning
confidence: 99%
See 2 more Smart Citations
“…However, these earlier studies did not distinguish between pedophilia and child sexual abuse. Recent reviews and meta-analyses investigating differences between individuals sexually oriented toward children and individuals sexually oriented toward adults revealed that their brain structures are very similar in nature (17,62,63). As indicated by two recent studies, aberrant neuroanatomy might rather be associated with child sexual abuse than with pedophilia (64,65).…”
Section: Structural Imagingmentioning
confidence: 99%
“…In accordance with this research, the Integrated Theory of Sexual Offending (ITSO), as one theoretical approach to explain sexual offending, provides a framework including an interaction between neurobiological and ecological factors (16). With respect to pedophilia, Tenbergen et al proposed a conceptual neurodevelopmental framework, with pedophilia as a complex and multifactorial phenomenon, in which the influences of genetics, stressful life events, specific learning processes, as well as structural brain changes may generate the specific phenotype of child sexual preference (17). In our review, however, we will solely concentrate on biological parameters.…”
Section: Biomarkers In Psychiatrymentioning
confidence: 99%
See 1 more Smart Citation
“…To further the understanding of potential neural dysfunctions underlying pedophilia and/or CSO the assessment of neuroimaging methods may be of high relevance. However, up to now, studies addressing the neurobiological correlates in this regard are scarce and most of them showed inconsistent results [Mohnke et al, ; Tenbergen et al, ]. The only replicated finding is limited to an amygdala volume reduction in offending pedophiles [Poeppl et al, ; Schiffer et al, ; Schiltz et al, ], although other authors using more stringent type‐1 error correction did not corroborate this result [Cantor et al, ; Cantor et al, ; Gerwinn et al, ], suggesting insufficient effect sizes of the aberrant amygdala volume.…”
Section: Introductionmentioning
confidence: 99%
“…No pathology was determined in cranial imaging, physical and neurological examinations in our patient, so organicity was ruled out. Some conditions which are believed to increase risk of pedophilic disorder development are summarized as prenatal androgen exposure, traumatic experiences during childhood (including sexual abuse), cranial trauma occurred before 13 years of age, low intelligent coefficient levels, decreased prefrontal and temporal inhibition, decreased volume in amygdala and hypothalamus (16). Traumatic experiences in childhood (sexual abuse) might be evaluated as the existent risk factor in our patient.…”
Section: Discussionmentioning
confidence: 99%